Counseling and Guidance on Communication Management Development of Religious Harmony with Global Competitiveness at Islamic Boarding Schools in Karawang Regency - Nurlaeli, Acep; Noor, H. E Tajuddin; Purnamaningsih, Ine Rahayu; Saputra, Suryana (Budapest International Research and Critics University, 2021)
The purpose of this study is to analyze the results of communication management development for the development of religious harmony with community outputs that can be globally competitive. This research uses qualitative method with descriptive analysis approach. The data used in this study are primary data and secondary data. Data collection techniques used are observation, interviews, and literature study. Data analysis of research results was carried out using qualitative methods. Based on the results of data and research analysis, it can be concluded that the communication management coaching and counseling activities at the Al-Fathimiyah Islamic Boarding School in Telukjambe Timur, Karawang District, focuses on 4 important factors, namely: context, inputs, process, and products.